Large scale germplasm screening for identification of novel rice blast resistance sources - Vasudevan, Kumar; Vera Cruz, Casiana M.; Gruissem, Wilhelm; Bhullar, Navreet K. (Frontiers in Plant Science, 2014)
Rice is a major cereal crop that contributes significantly to global food security. Biotic stresses, including the rice blast fungus, cause severe yield losses that significantly impair rice production worldwide. The rapid genetic evolution of the fungus often overcomes the resistance conferred by major genes after a few years of intensive agricultural use. Therefore, resistance breeding requires continuous efforts of enriching the reservoir of resistance genes/alleles to effectively tackle the disease. Seed banks represent a rich stock of genetic diversity, however, they are still under-explored for identifying novel genes and/or their functional alleles. We conducted a large-scale screen for new rice blast resistance sources in 4246 geographically diverse rice accessions originating from 13 major rice-growing countries. The accessions were selected from a total collection of over 120’000 accessions based on their annotated rice blast resistance information in the International Rice Genebank. A two-step resistance screening protocol was used involving natural infection in a rice uniform blast nursery and subsequent artificial infections with five single rice blast isolates. The nursery-resistant accessions showed varied disease responses when infected with single isolates, suggesting the presence of diverse resistance genes/alleles in this accession collection. In addition, 289 accessions showed broad-spectrum resistance against all five single rice blast isolates. The selected resistant accessions were genotyped for the presence of the Pi2 resistance gene, thereby identifying potential accessions for isolation of allelic variants of this blast resistance gene. Together, the accession collection with broad spectrum and isolate specific blast resistance represent the core material for isolation of previously unknown blast resistance genes and/or their allelic variants that can be deployed in rice breeding programs.